2021
DOI: 10.1007/s11301-021-00251-8
|View full text |Cite
|
Sign up to set email alerts
|

Corporate tax risk: a literature review and future research directions

Abstract: Our study aims to analyze the current state of, and avenues for, future studies into the tax risk literature. The construct of the corporate tax risk (tax uncertainty) has increasingly begun to attract significant interest from both academics and practitioners. Most previous studies discussing corporate tax behavior have also focused on tax planning, tax avoidance, and tax evasion. Studies investigating the tax risk are still very limited and it is an underexplored subject. Examining the tax risk is crucial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 95 publications
2
19
0
Order By: Relevance
“…Policymakers can require minimum disclosures about unrecognized tax benefits in a company's annual report. In the USA, for example, firms have been required to submit reports on unrecognized tax benefits (Saragih and Ali, 2021). Adequate disclosure of unrecognized tax benefits in the annual report is expected to prevent companies from engaging in illegal tax savings practices that expose them to certain tax risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Policymakers can require minimum disclosures about unrecognized tax benefits in a company's annual report. In the USA, for example, firms have been required to submit reports on unrecognized tax benefits (Saragih and Ali, 2021). Adequate disclosure of unrecognized tax benefits in the annual report is expected to prevent companies from engaging in illegal tax savings practices that expose them to certain tax risks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future Notes: a Robust standard error is used due to the nonnormality and heteroscedasticity of residuals; b Panel regression using the fixed effect method; Ã , ÃÃ and ÃÃÃ represent significance at levels 0.10, 0.05 and 0.01 research can replicate this study using the same or a similar basic research model, but with moderating or mediating variables added. The expansion of the corporate tax behaviours research model route will contribute to theory, literature and practice in a relatively new way (Saragih and Ali, 2021). Re-examination will be useful for synthesizing, combining and expanding knowledge of specific phenomena (Block et al, 2022), which will ultimately help to place academic discussions on a solid foundation because it is supported by a variety of empirical evidence (Block and Kuckertz, 2018).…”
Section: Conclusion Limitations and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most recent research focuses on the direct impact of XBRL adoption, our study is among the first to propose and test an explanation for the moderating role of XBRL adoption on the association between managerial ability and corporate tax avoidance and tax risk. Finally, this study Empirical evidence from Indonesia responds to Saragih and Ali (2021) who suggested examining the impact of XBRL on tax avoidance and tax risk in non-US countries.…”
Section: Empirical Evidence From Indonesiamentioning
confidence: 93%
“…The relationship between CTA and FV has been studied in the literature from the perspective of developed countries, but it is an under-researched issue from the perspective of developing countries (Saragih & Ali, 2021). Furthermore, the inconclusive results in the literature provide the opportunity to further investigate the association (Salihu & Kawi, 2021).…”
Section: Introductionmentioning
confidence: 99%